Usability testing on motion sensing video game for elderly / Lokman Hakim Jamil - Jamil, Lokman Hakim (2013)
Video games have been a popular leisure activity among children, teenagers and young adults. However, with the availability of new consoles aimed at casual gamers, different target audiences have been addressed including elderly people. Today, video games have evolved with the emergence of motion sensing technology that uses body gestures as a controller. The purpose of this study is to identify the user experience on motion sensing video game among elderly in Malaysia context. There are some researches had been done on motion sensing game for elderly but none had been focusing on Malaysian elderly. Various studies had shown that these ageing or greying population are increasing in many developing countries including Malaysia. Thus, social as well as economic considerations suggest that they must be considered in the development of current and future technologies. This study focuses on usability testing. Observations and interviews with six participants in Kampung Felda Bukit Batu, Kulai, Johor were used in this study. The experience with gaming, usability issues, feedbacks and suggestions were covered in this study. From the usability testing it is found that some considerations need to be taken into account such as language barrier, gesture understanding and elderly physical condition. From the feedback of the elderly, it is suggested that bilingual option should be included and simplified interface are also taken into considerations. The results of this study will contribute for future research on elderly interaction with motion sensing technology.